1998
DOI: 10.1002/(sici)1520-6858(1998)1:3<176::aid-sys3>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Systems integration and architecting: An overview of principles, practices, and perspectives

Abstract: Systems Integration is an activity omnipresent in almost all of systems engineering and management. Often the term lacks precise definition and is used in different ways and for different purposes in the engineering of systems. This paper presents an overview of systems integration at all levels of system engineering and management. The goal of the paper is to present the various views of systems integration including lifecycle, architecture, process, interface, and enterprise, as well as product integration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 20 publications
(23 reference statements)
0
48
0
Order By: Relevance
“…For Sage and Lynch (1998), the integration of technical parameters and interface compatibility are generally assumed as a technical effort carried out during the latter parts of the system development lifecycle. However, if this effort is not planned properly in the definition phases and in the early parts of the development phase, integration is likely to be difficult at the end of the development phase.…”
Section: Issn: 2349-6495(p) | 2456-1908(o)mentioning
confidence: 99%
See 1 more Smart Citation
“…For Sage and Lynch (1998), the integration of technical parameters and interface compatibility are generally assumed as a technical effort carried out during the latter parts of the system development lifecycle. However, if this effort is not planned properly in the definition phases and in the early parts of the development phase, integration is likely to be difficult at the end of the development phase.…”
Section: Issn: 2349-6495(p) | 2456-1908(o)mentioning
confidence: 99%
“…In this way, Sage and Lynch (1998) suggested that if we consider that the activities of analysis, definition, design, requirements and control of interfaces are all integration efforts, then the system integration occurs at almost every stage of the systems development lifecycle, not just in its later stages.…”
Section: Issn: 2349-6495(p) | 2456-1908(o)mentioning
confidence: 99%
“…The technical view is a set of rules defining the interactions and interdependencies of system elements to assure compatibility and satisfaction of requirements. The system view describes the physical connections, locations, key nodes, etc, needed to support enterprise functions (23) . Transformation of work processes inherently must affect the operational view of the architecture.…”
Section: Enterprise Transformationmentioning
confidence: 99%
“…[ Sage-Lynch 1998] stress "the important role that architecture plays in system integration." They present the need for three major views: enterprise view, systems engineering and management view, and technology implementation view -and they stress to ensure consistency among these views.…”
Section: Related Workmentioning
confidence: 99%